(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
The removal of heat from system components is essential to avoid damaging effects of burning and heating. Therefore the enhancement of heat transfer is an important subject in thermal engineering. Thermal insulators are often used in heat exchanging devices for increase in heat transfer. Over the years many theists’ have tried to find efficient and safe means to establish thermal insulation between heat generating systems. This report mainly focuses on heat transfer through systems working on a low heat input. The materials used in this experimental project are available in abundance around us. In this paper, the thermal conductivity for the insulating powders have been determined viz., rice husk, rice bran, paddy straw, millet husk, millet straw, jute and combinations. These materials are freely available in nature and are extremely safe when exposed to heat. Mixture of these materials with any sort of resin can be used as an effective heat insulator. The experimental study deals with the estimation of thermal conductivity of various materials in its powdered form. The intermittent temperature values are used to find thermal conductivity. Different trials are conducted using different materials and their mixtures. The study is done at different heat inputs. Comparison between the heat input and the thermal conductivity has been accounted.